2005
DOI: 10.1038/sj.onc.1208581
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-releasing peptide (GRP) induces angiogenesis and the specific GRP blocker 77427 inhibits tumor growth in vitro and in vivo

Abstract: Angiogenesis is becoming a major target for antitumor therapies, and identifying new angiogenic factors and their specific inhibitors may provide new avenues for tumor management. Here we identify gastrin-releasing peptide (GRP) as a new angiogenic molecule that is secreted by tumors and acts directly upon GRP receptors in the endothelial cells. Addition of GRP increases endothelial cell migration and cord formation in vitro, and induces angiogenesis in an in vivo assay. We have recently identified a small mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
7
33
0
1
Order By: Relevance
“…To explore the possible regulation of angiogenesis by bombesin-like peptides, we used the Matrigel assay of capillary tubulogenesis. We demonstrated that bombesin increases capillary tubulogenesis of pulmonary microvascular endothelial cells cultured alone, consistent with other reports of proangiogenic effects of GRP (49). However, cocultured mesenchymal cells reverse bombesininduced angiogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…To explore the possible regulation of angiogenesis by bombesin-like peptides, we used the Matrigel assay of capillary tubulogenesis. We demonstrated that bombesin increases capillary tubulogenesis of pulmonary microvascular endothelial cells cultured alone, consistent with other reports of proangiogenic effects of GRP (49). However, cocultured mesenchymal cells reverse bombesininduced angiogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…1D) had fewer macrophages and neutrophils (PMN) than controls (PBS or MOPC, P < 0.002). MOPC is the ideal isotype (IgG1)-matched negative control for 2A11, controlling for nonspecific protein binding and effects from Fc-gamma receptor binding (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…Direct effects are also likely in airway smooth muscle constriction (21,22), endothelial cell activation and angiogenesis (20,41), and epithelial cell and fibroblast proliferation (6, 31, 52) during remodeling. Indirect effects due to increased cytokine production could occur in parallel, some cytokines being secreted earlier due to direct binding of GRP to GRPR on target cells, amplifying proinflammatory signals via multiple cytokinespecific receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of these G-protein-coupled receptors to their respective ligands results in the activation of multiple proliferative signaling cascades [23,24]. GRP also seems to have angiogenic properties, inducing endothelial-cell migration and cord formation in vitro, and promotion of angiogenesis in vivo [25].…”
Section: Gastrin-releasing Peptidementioning
confidence: 99%